2019
DOI: 10.1159/000498854
|View full text |Cite
|
Sign up to set email alerts
|

Higher in vivo Cortical Intracellular Volume Fraction Associated with Lithium Therapy in Bipolar Disorder: A Multicenter NODDI Study

Abstract: Background: MRI studies in patients with bipolar disorder have suggested that lithium is associated with grey matter increases that may underlie its therapeutic effects. However, the relationship between grey matter volume and cellular microstructural changes is not straightforward, as modifications of different cellular compartments of grey matter may be involved. Objectives: Our aim was to test the hypothesis that dendritic density is higher in patients undergoing lithium therapy than in patients without lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Consequently, to build more precise neurobiological models of BD future studies should benefit from new advanced neuroimaging methods such as Neurite Orientation Dispersion and Density Imaging (NODDI) [41]. This recent processing model allows fine-grained measurement of the WM microstructure, with physiological interpretation of the derived indices, and has already shown promising results in BD [42]. However, the large-scale application of such methods will only be possible with raw data sharing within international consortia.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, to build more precise neurobiological models of BD future studies should benefit from new advanced neuroimaging methods such as Neurite Orientation Dispersion and Density Imaging (NODDI) [41]. This recent processing model allows fine-grained measurement of the WM microstructure, with physiological interpretation of the derived indices, and has already shown promising results in BD [42]. However, the large-scale application of such methods will only be possible with raw data sharing within international consortia.…”
Section: Discussionmentioning
confidence: 99%
“…Given that many patients included in our meta-analysis were undergoing medication at the time of the scan (Table S4), this variable is likely to have some impact on the COA-O network. However, there is some evidence that suggests that medication alone is unable to explain our results: first, morphological effects of medication are often found to be localized to restricted regions, such as medial temporal lobe and subgenual cortex with lithium (Germaná et al, 2010;Hafeman et al, 2012) and BG with antypsichotics (Navari and Dazzan, 2009), while our increase nodes are situated in many other brain areas; second, some studies report that medications could attenuate pathological decreases rather than increase GM volume in patients compared to controls (Sheline et al, 2003;Wada et al, 2005;Hibar et al, 2016;Zung et al, 2016;Sarrazin et al, 2019); third, atypical antipsychotics, although found by some to be neurotrophic and induce neurogenesis (Wakade et al, 2002;Bai et al, 2003;Halim et al, 2004;Wang et al, 2004;Park et al, 2006) produced mixed volumetric findings (Massana et al, 2005;Navari and Dazzan, 2009) but often no increase effects were found in the BG (Chakos et al, 1995;Frazier et al, 1996;Westmoreland Corson et al, 1999;Lang et al, 2001Lang et al, , 2004Scheepers et al, 2001).…”
Section: Discussionmentioning
confidence: 79%
“…Candidate mechanisms for increased GM include modifications to neuronal tissue, such as neurogenesis (Eriksson et al, 1998), synaptogenesis (Sarrazin et al, 2019) or changes in somal size and density, in addition to changes in glia (Rocha et al, 1998) or neurovasculature (Zatorre et al, 2012). There could be diverse causes of such modifications, which may be related to inflammatory processes (Poletti et al, 2019) that might, for instance, induce astrocytic hypertrophy (Li et al, 2019), or to activity-driven volumetric increases similar to those observed during learning (Zatorre et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…9 This discrepancy could be related with treatment, since another study reported that patient with bipolar affective disorder without lithium therapy showed lower ND in the left frontal cortex than those with lithium as well as than healthy controls. 60 Thus, there are already several studies of NODDI and several common psychiatric disorders, suggesting a future clinical use for NODDI. However, psychiatric disorders and symptoms are highly diverse and remain to be fully elucidated in neuroimaging studies.…”
Section: Psychiatric Disordersmentioning
confidence: 99%